2019
DOI: 10.4236/ojfd.2019.92009
|View full text |Cite
|
Sign up to set email alerts
|

CFD Assisted Study of Multi-Chapels Greenhouse Vents Openings Effect on Inside Airflow Circulation and Microclimate Patterns

Abstract: The aim of this work is to study and quantify the air mass flow exchanged between inside and outside of the greenhouse, in order to determine the ventilation openings layout and the design effect on greenhouse airflow and microclimate distribution. The study was conducted over a 945 m 2 multi-chapels arched greenhouse with a polyethylene cover and has thirteen crop rows oriented from north to south; the greenhouse was equipped with side wall and roof vents openings. A simulation was performed using different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…The heat distribution fields for scenarios S8, S11 and S14 under external wind speed simulations V1, V3 and V5 are shown in Figure 9. How the temperature distribution depends on the flow field and ventilation rates [48], it can be observed that as these parameters did not present significant changes compared to scenarios S1 to S7, this translates into similar thermal distributions, where the colder zones agree with the fresh and less dense air intake zones of the environment and outside and the warmer zones with the zones of lesser air movement or air flow exit zones, which is consistent with similar studies such as the one carried out by Senhaji et al, [49].…”
Section: Wind Direction Sw-nesupporting
confidence: 89%
“…The heat distribution fields for scenarios S8, S11 and S14 under external wind speed simulations V1, V3 and V5 are shown in Figure 9. How the temperature distribution depends on the flow field and ventilation rates [48], it can be observed that as these parameters did not present significant changes compared to scenarios S1 to S7, this translates into similar thermal distributions, where the colder zones agree with the fresh and less dense air intake zones of the environment and outside and the warmer zones with the zones of lesser air movement or air flow exit zones, which is consistent with similar studies such as the one carried out by Senhaji et al, [49].…”
Section: Wind Direction Sw-nesupporting
confidence: 89%
“…In the computational domain, the physical and optical properties of the materials described in Table 1 were used, taking the reference values used in the work carried out by Senhaji et al [47]. On the other hand, in these 13 simulations a power absorption coefficient (αλ) was established to obtain a transmittance of zero for long wavelengths and 0.8 for short wavelengths.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…It is also observed that in spans 3, 4 and 5 the airflow patterns enter with a low velocity of approximately 0.23 ms −1 , and then accelerate to a velocity of 0.67 ms −1 as these airflows ascend the slope of the terrain. This acceleration of the airflow may be influenced by the convective effect caused by changes in density as a function of the change in temperature of the air inside the structure [47].…”
Section: Qualitative and Quantitative Characteristics Of Airflow Patternsmentioning
confidence: 99%
“…The air exchange rate of a naturally ventilated structure is a parameter that allows measuring the efficiency of the ventilation system, this rate is defined as the relationship between the volumetric rate of air flow exiting the structure and the volume of the structure, this value was calculated by integration method mass flow rate (Senhaji et al, 2019;Villagrán et al, 2019).…”
Section: Indexes Of Hourly Renewalmentioning
confidence: 99%
“…In MPG, by obtaining higher renewal rates and better airflow movement, an additional thermal distribution of lower magnitude and more homogeneous compared to PG is obtained (Figure 10). This is a relevant result since sometimes a higher ventilation rate does not necessarily generate a reduction of the temperature value inside the structure and a greater homogeneity, this happens when the optimization strategies of natural ventilation do not generate adequate air flows inside the greenhouse, especially in the area where the crop will be established (Sase, 2006;Senhaji et al, 2019). The average values of temperature (MT) and thermal differential between outside and inside (∆T m ) were calculated for each of the simulated scenarios and for the two heights analyzed (Table 4).…”
Section: Thermal Behaviourmentioning
confidence: 99%